Respons Pertumbuhan Bibit Kakao (Theobroma cacao L.) terhadap Pemberian Dosis Slurry pada Ultisols Hajimena - Lurfhia Haida Hakim; Rijadi Subiantoro; Fatahillah Fatahillah (Jurnal Agro Industri Perkebunan, 2019)
This study aims to obtain the best slurry dosage for the growth of cocoa seedlings. This reaserch was conducted in the experimental garden, chemical analyzed laboratory, and soil laboratory of Politeknik Negeri Lampung on November 2017 until March 2018. The method used was a Completely Randomized Design (CRD) with 6 doses of slurry (0 ml, 80 ml, 160 ml, 240 ml, 320 ml, and 400 ml). Observation variables in the form of premilinary observations abd observations during the study. Preliminary observations analyzed the levels of N, P, K, pH, and C-Organic on topsoil and slurry. Obsevation during the study were plant height, stem diameter, number of leaves, dry weight of shoot dry weight, root dry weight, and moisture content. The results showed that slurry doses did not affect on the cocoa seedling growth.